Essential and toxic elements analysis of wild boar tissues from north-eastern Romania and health risk implications - Boișteanu, Paul-Corneliu; Flocea, Elena-Iuliana; Anchidin, Bianca-Georgiana; Mădescu, Bianca-Maria; Matei, Mădălina; Murariu, Otilia Cristina; Frunză, Gabriela; Postolache, Alina Narcisa; Ciobanu, Marius-Mihai (Frontiers in Sustainable Food Systems, 2024)
Introduction The level of essential minerals in meat is an important factor in human nutrition and health. Meat from responsibly managed wildlife is an alternative raw material with considerable nutritional benefits. Meat from hunted animals has essential and non-essential elements for the human body. It is important to carefully monitor the levels of heavy metals accumulated in the tissues of hunted animals in polluted areas to ensure food safety and environmental contamination. High levels of heavy metals in food and the environment can pose a danger to human health. Methods The study aims to investigate the levels of essential mineral elements and heavy metals in the muscle tissue and organs of wild boar harvested through the herd density control plan over the last decade in north-eastern Romania. Results and discussion The statistical analysis indicates that the age of the animals had a significant impact on Fe, Cu, and Zn levels in Longissimus lumborum. In the kidney a highly significant difference in Fe content by sex, with males showing higher values than females. The sex was shown to significantly influence the Mg levels. However, there are concerns about the accumulation of heavy metals such as Lead (Pb) and Cadmium (Cd), which may hurt the health of game meat consumers in the study area. Cd level it shows significant differences according to both age and sex, with higher concentrations in adults and males. Statistical analysis shows a negative correlation between Fe and Zn concentrations in muscle samples, while a positive correlation was found between Fe and Mn in kidney samples. There was also a positive association between Zn and Cu in muscle samples, but a negative association in kidney samples. Principal component analysis shows significant variation in essential element and heavy metals data between muscle and kidney samples. The loading plot shows a direct correlation between Pb and Cu and between Pb and Cd. However, an opposite correlation also is observed between Cu and Mg, Cd and Mg, and Pb and Mg. HQ (Hazard Quotient) for children compared to adults indicates a potentially higher risk associated with meat consumption among children because children are more vulnerable than adults. We report for the first time, to the best authors’ knowledge, various levels of essential minerals and exceeded maximum admitted level of heavy metals in the muscle tissues and kidneys of Sus scrofa ferus from Romania intended for human consumption, moreover, our findings highlight the need for strict monitoring and implementation of appropriate corrective measures, given the significant percentages of muscle and kidney samples exceeding the allowable limits for two of the most common toxic metals in the environment.